2008
DOI: 10.1007/s10620-008-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Kampo Medicine “Dai-Kenchu-To” Prevents Bacterial Translocation in Rats

Abstract: Kampo medicine "Dai-kenchu-to" (DKT) has been used for treatment of ileus. The aim of this study was to evaluate the role of DKT on the bacterial translocation (BT) model in rats. Rats were divided into the following four groups: group 1, receiving only water, and groups 2, 3, and 4, receiving 100, 300, and 1,000 mg/kg/day of DKT. Rats were sacrificed 6 days after the beginning of the fast, and then the mesenteric lymph node was cultured. Inflammatory cytokines, intestinal integrity, and apoptosis were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
(50 reference statements)
3
34
0
Order By: Relevance
“…Results from a recent clinical pharmacological study have shown that TJ-100 accelerates intestinal transit in healthy humans (Manabe et al, 2010). Furthermore, basic pharmacological studies have suggested that TJ-100 and its ingredients have a wide variety of biological effects, including a prokinetic effect largely attributed to the activity of Zanthoxylum piperitum fruit (Jin et al, 2001;Kawasaki et al, 2007;Tokita et al, 2007a,b), contraction and relaxation of intestinal smooth muscle (Kito and Suzuki, 2006), an increase in intestinal blood flow due to the activity of ginger ingredients (Murata et al, 2002;Kono et al, 2008), an anti-inflammatory effect (Kono et al, 2010), and suppression of bacterial translocation possibly mediated by ginseng ingredients (Yoshikawa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Results from a recent clinical pharmacological study have shown that TJ-100 accelerates intestinal transit in healthy humans (Manabe et al, 2010). Furthermore, basic pharmacological studies have suggested that TJ-100 and its ingredients have a wide variety of biological effects, including a prokinetic effect largely attributed to the activity of Zanthoxylum piperitum fruit (Jin et al, 2001;Kawasaki et al, 2007;Tokita et al, 2007a,b), contraction and relaxation of intestinal smooth muscle (Kito and Suzuki, 2006), an increase in intestinal blood flow due to the activity of ginger ingredients (Murata et al, 2002;Kono et al, 2008), an anti-inflammatory effect (Kono et al, 2010), and suppression of bacterial translocation possibly mediated by ginseng ingredients (Yoshikawa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5 Injury score. CPT-11 alone caused a significant increase in the injury score, which was significantly lower in the DKT group than in the CPT-11 group (*P \ 0.05) by inhibiting the production of inflammatory cytokines, including IFN-c, IL-6, and TNF-a, and alleviated intestinal epithelial apoptosis significantly [11]. Although it has not yet been proved that DKT prevents the side effects induced by chemotherapy, it is inexpensive and has few side effects.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies show that DKT accelerates the gastrointestinal transit [10] and has an anti-inflammatory effect. We reported recently that DKT prevents bacterial translocation by reducing inflammatory reaction and maintaining intestinal integrity [11]. We conducted this study to examine the effect of DKT on CPT-11-induced small-intestinal injury in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, other effects of DKT have been reported; it induces increases in intestinal blood flow [12], reduces the blood ammonia level after hepatectomy [13], and has anti-inflammatory effects [14]. We previously reported that DKT prevented BT by maintaining the intestinal barrier integrity through its anti-inflammatory and antiapoptotic effects in a rat BT model [15]. We hypothesized that DKT may also prevent the inflammatory response in postoperative patients.…”
Section: Introductionmentioning
confidence: 98%